Evolution of sigma phase precipitates in Cu-containing 25Cr–20Ni austenitic stainless steels - Gunjick Lee; Heechan Jung; Han Jun Yu; Jung Hun Han; Seok Su Sohn; Jae-Hyeok Shim (Journal of Materials Research and Technology)
This study investigated, for the first time, the influence of Cu addition on sigma phase precipitation during aging at 700 °C in recrystallized 25Cr–20Ni austenitic stainless steels containing up to 2.9 wt% Cu. The sigma phase degrades the mechanical properties of steels. Microstructural analyses showed that Cu addition significantly reduced sigma precipitation during aging for up to 1,000 h. However, in the early stages of aging, the amount of the sigma phase was slightly higher in the Cu-containing samples than in the sample without Cu. The amount of the sigma phase in the samples aged for 1,000 h was reduced 15.3, 8.8 and 7.6 % in the samples with 0, 1.4, and 2.9 wt% Cu, respectively. Interestingly, Cu-enriched layers were observed around sigma phase precipitates, which were presumed to consist of Cu atoms expelled from sigma phase precipitates with very limited Cu solubility. These layers seemed to play a crucial role in retarding the growth of the sigma phase in the samples with Cu. Tensile test results for the samples aged for 1,000 h indicated that the elongation of all the samples was significantly reduced compared to that of the recrystallized samples owing to the sigma phase precipitation. Nevertheless, the elongation losses of the samples with 1.4 and 2.9 wt% Cu were much smaller than those of the sample without Cu.